2005
DOI: 10.1541/ieejpes.125.1077
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polymer Vapor Concentration on Temperature of Ar Induction Thermal Plasmas During Polymer Solid Powder Injections

Abstract: Influence of POM (polyoxymethylene), PE (polyethylene) and PMMA (polymethylmethacrylate) polymer solid powder injections on thermal plasmas was experimentally investigated for the fundamental study of ablation phenomena in a circuit breaker. For this purpose, the inductively coupled thermal plasma (ICTP) technique was used to sustain Ar thermal plasmas at atmospheric pressure at a high-power of 80 kW. Spectroscopic observation was carried out to measure the radiation intensity of Ar I, H I and C I lines emitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Among the four polymers, PMMA vapor produced the best cooling effect on the thermal plasma; specifically, it was found that a strong cooling effect was produced by an equivalent increase of the specific heat due to ionization of the polymer vapor at temperatures of 1000 to 2000 K [12,13]. On the other hand, as explained above, plasma cooling has little direct dependence on the heat required for melting and ablation.…”
Section: Effect Of Thermal Properties Of Ablated Vapor and Solid Polymentioning
confidence: 91%
“…Among the four polymers, PMMA vapor produced the best cooling effect on the thermal plasma; specifically, it was found that a strong cooling effect was produced by an equivalent increase of the specific heat due to ionization of the polymer vapor at temperatures of 1000 to 2000 K [12,13]. On the other hand, as explained above, plasma cooling has little direct dependence on the heat required for melting and ablation.…”
Section: Effect Of Thermal Properties Of Ablated Vapor and Solid Polymentioning
confidence: 91%
“…We have already used inductively coupled thermal plasmas (ICTPs) for a fundamental study of various gas or polymer-ablated vapour effect on the temperature of highpressure thermal plasmas, neglecting effects of pressure rise and gas flow jet [17][18][19][20][21]. The ICTP presents the crucial advantage of no contamination because it uses no electrode, as does either dc or ac arc plasma.…”
Section: Introductionmentioning
confidence: 99%
“…It also has features of a good repeatability and controllability for experimental conditions. These advantages and features facilitate the investigation of the inherent characteristics of polymer-ablated vapours themselves on physical parameters of thermal plasmas such as the radiation intensity and the Ar excitation temperature [17,19,20]. In those experiments, polymer solid powders were actually injected into Ar induction thermal plasmas; then spectroscopic observations were carried out [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…We have proposed the use of an inductively coupled thermal plasma (ICTP) technique for the fundamental study of the interactions between cold gas and thermal plasmas [1] and between solid powder and thermal plasmas [2], [3] to produce pure thermal plasmas with few impurities, which is favorable for this fundamental investigation. This paper reports the visualization of the spatial distribution of polymer-ablated vapor in ICTP with polymer powder.…”
mentioning
confidence: 99%
“…The plasma torch used here is the same torch with a threeturn induction coil used in our previous work [2]. Argon was supplied as a sheath gas, with a gas flow rate of 100 l/min.…”
mentioning
confidence: 99%